Intermittent hemodiafiltration as a down-step transition therapy in patients with acute kidney injury admitted to intensive care unit who initially underwent continuous venovenous hemodiafiltration. Issue 4 (April 2021) - Scherer, Patricia Faria; Iizuka, Ilson Jorge; Ammirati, Adriano Luiz; Doher, Marisa Petrucelli; Matsui, Thais Nemoto; dos Santos, Bento Fortunato Cardoso; Monte, Julio Cesar Martins; Batista, Marcelo Costa; Pereira, Virgilio Gonçalves; dos Santos, Oscar Fernando Pavão; Durão, Marcelino de Souza
Background/Aims: Continuous renal replacement therapies (CRRT) are initially employed in patients with acute kidney injury (AKI) in ICU setting. After the period of serious illness, hemodialysis is usually used as a mode of transition from CRRT. Intermittent hemodiafiltration (HDF) is not commonly applied in this scenario. Objectives: To evaluate the feasibility of using HDF as transition therapy after CVVHDF in critically patients with AKI. Methods: An observational and prospective pilot study was conducted in ICU patients with dialysis-requiring AKI. Patients were initially treated with CVVHDF and, after medical improvement, those who still needed renal replacement therapy were switched to HDF treatment. Results: Ten Patients underwent 53 HDF sessions (mean of 5.3 sessions/patient). The main cause of renal dysfunction was sepsis ( N = 7; 70%). The APACHE II mean score was 27.6 ± 6.9. During HDF treatment, the urea reduction ratio was 64.5 ± 7.5%, for β-2 microglobulin serum levels the percentage of decrease was 42.0 ± 7.8%, and for Cystatin C was 36.2 ± 6.9%. Five episodes of arterial hypotension occurred (9.4% of sessions). There were 20 episodes of electrolytic disturbance (37.7% of sessions), mainly hypophosphatemia. No pyrogenic or suggestive episode of bacteremia was observed. Conclusion: Hemodiafiltration was safe and efficient to treat critically ill patients with acute kidney injury during the transition phase from continuous to intermittent dialysis modality. Special attention should be paid regarding the occurrence of electrolytic disturbance, mainly hypophosphatemia.